Genomics England's implementation of its public engagement strategy: Blurred boundaries between engagement for the United Kingdom's 100, 000 Genomes project and the need for public support. (April 2018) - Samuel, Gabrielle Natalie; Farsides, Bobbie
The United Kingdom's 100, 000 Genomes Project has the aim of sequencing 100, 000 genomes from National Health Service patients such that whole genome sequencing becomes routine clinical practice. It also has a research-focused goal to provide data for scientific discovery. Genomics England is the limited company established by the Department of Health to deliver the project. As an innovative scientific/clinical venture, it is interesting to consider how Genomics England positions itself in relation to public engagement activities. We set out to explore how individuals working at, or associated with, Genomics England enacted public engagement in practice. Our findings show that individuals offered a narrative in which public engagement performed more than one function. On one side, public engagement was seen as 'good practice'. On the other, public engagement was presented as core to the project's success – needed to encourage involvement and ultimately recruitment. We discuss the implications of this in this article.